Proceedings of the 2nd Workshop on Computational Linguistics and Clinical Psychology: From Linguistic Signal to Clinical Realit 2015
DOI: 10.3115/v1/w15-1201
|View full text |Cite
|
Sign up to set email alerts
|

From ADHD to SAD: Analyzing the Language of Mental Health on Twitter through Self-Reported Diagnoses

Abstract: Many significant challenges exist for the mental health field, but one in particular is a lack of data available to guide research. Language provides a natural lens for studying mental health-much existing work and therapy have strong linguistic components, so the creation of a large, varied, language-centric dataset could provide significant grist for the field of mental health research. We examine a broad range of mental health conditions in Twitter data by identifying self-reported statements of diagnosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
272
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 274 publications
(284 citation statements)
references
References 36 publications
8
272
1
3
Order By: Relevance
“…We use the entire Twitter history of each user as input to the model, and split it into character 1-to-5-grams, which have been shown to capture more information than words for many Twitter text classification tasks (Mcnamee and Mayfield, 2004;Coppersmith et al, 2015a). We compute the relative frequency of the 5,000 most frequent n-gram features for n ∈ {1, 2, 3, 4, 5} in our data, and then feed this as input to all models.…”
Section: Datamentioning
confidence: 99%
See 2 more Smart Citations
“…We use the entire Twitter history of each user as input to the model, and split it into character 1-to-5-grams, which have been shown to capture more information than words for many Twitter text classification tasks (Mcnamee and Mayfield, 2004;Coppersmith et al, 2015a). We compute the relative frequency of the 5,000 most frequent n-gram features for n ∈ {1, 2, 3, 4, 5} in our data, and then feed this as input to all models.…”
Section: Datamentioning
confidence: 99%
“…We are the first to apply MTL to predict mental health conditions from user content on Twitter -a notoriously difficult task (Coppersmith et al, 2015a;Coppersmith et al, 2015b). 2.…”
Section: Our Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2015 CLPsych Shared Task consisted of three user-level binary classification tasks: PTSD vs. control, depression vs. control, and PTSD vs. depression. The first two have been addressed in a number of settings (Coppersmith et al, 2015;Coppersmith et al, 2014b;Coppersmith et al, 2014a;Resnik et al, 2013;De Choudhury et al, 2013;Rosenquist et al, 2010;Ramirez-Esparza et al, 2008), while the third task is novel. Organizing this shared task brought together many teams to consider the same problem, which had the benefit of establishing a solid foundational understanding, common standards, and a shared deep understanding of both task and data.…”
Section: Introductionmentioning
confidence: 99%
“…Inferring demographic attributes has thus been a frequent area of research Pennacchiotti and Popescu, 2011;Volkova, 2015;Rao and Yarowsky, 2010;Mislove et al, 2011), enabling large-scale analysis of demographically identified social media posts. Demographic inference has been used in many Twitter analyses, including studies of mental health (Coppersmith et al, 2015), exercise (Dos Reis and Culotta, 2015), language (Eisenstein et al, 2011; and personality (Schwartz et al, 2013).…”
Section: Introductionmentioning
confidence: 99%